Tipos de alimentación y ganancia de peso en neonatos. Hospital “La Caleta”, Chimbote. - Suarez Villanueva, Sthefanie Gabriela (2020)
The research is quantitative descriptive correlational type was aimed at determining the relationship between the type of feeding and weight gain in neonates. The sample universe was made up of a total of 30 newborns. Data collection was carried out with the application of three instruments: the “Pre-term and term newborn type of feeding and weight gain record card” (FRTAGPRNPTYAT), Fenton 2013 intrauterine growth curve for males (CCIUFRNPTM) , Fenton 2013 intrauterine growth curve for females (CCIUFRNPTF). For the statistical analysis, the criteria independence test (chi square) was applied. The following conclusions were obtained: 36.7% of infants fed the milk formula, 30%, exclusive human milk, 23.3% of infants, mixed milk and only 10% consumed fortified human milk. 63.3% of newborns showed adequate weight gain and 36.7%, inadequate weight gain, showing that there is a significant relationship between the type of feeding and weight gain, p <0.05.